APLIKASI COMPUTER VISION PADA KUALITAS KEMATANGAN BUAH - AGUSTIYANTO, FRANS RIZAL (Sainstek : Jurnal Sains dan Teknologi, 2012)
This paper introduces the computer vision with the comparison of color methods to classify the variants of fruit (tomatoes, chilies, and apples) which is based on the level or stage of ripe.  The color comparison method is quite simple; the tomato images captured by the camera (CCD) will be cropped partly. Then its characteristic color will be extracted and the color grade level will be calculated. The calculation of R (red), G (green) and B (blue) and the transformation of the color to Hue, Saturation, and Value was conducted in order to classify the fruit maturity. Thus, the ripe can be classified into 3, namely Ripe, Half-Ripe, and Un-ripe (not ripe). On contrary, over-ripe cannot be classified because the characteristics of the color is similar with the ripe tomato but the skin texture is slack, so it is not enough to characterize the color used to draw conclusion of being Over-ripeKey words: image processing, computer vision, RGB, HVS